1999
DOI: 10.1046/j.1365-3121.1999.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

The Early Cretaceous drowning unconformities of the Apulia carbonate platform (Gargano Promontory, southern Italy): local fingerprints of global palaeoceanographic events.

Abstract: Drowning successions which cap carbonate platforms and flanks bear palaeoenvironmental information which is useful for genetic stratigraphy; they constitute predictive key‐markers in regional to global correlations. An Early Cretaceous platform‐to‐basin transition has been investigated in Apulia (southern Italy) and two drowning unconformities, dated as early Valanginian and late early Aptian, have been documented. They occur at the base of thick pelagic tongues wedging toward the platform and mark the base of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 28 publications
1
21
0
12
Order By: Relevance
“…The southern part of the Gargano Promontory is well‐known for its spectacular deposits of platform‐slope limestones that form large megabreccias containing shallow‐water lithoclasts supported by finer‐grained, shallow‐marine bioclastic grainstones and foraminifera mudstones (Morsilli & Bosellini, ; Bosellini et al ., ; Graziano, ; Hairabian et al ., ). These deposits are regarded as the product of repeated collapse of the platform margin, possibly induced by synsedimentary extensional faulting (Graziano, , ; Borgomano, ).…”
Section: Study Area and Methodologymentioning
confidence: 99%
“…The southern part of the Gargano Promontory is well‐known for its spectacular deposits of platform‐slope limestones that form large megabreccias containing shallow‐water lithoclasts supported by finer‐grained, shallow‐marine bioclastic grainstones and foraminifera mudstones (Morsilli & Bosellini, ; Bosellini et al ., ; Graziano, ; Hairabian et al ., ). These deposits are regarded as the product of repeated collapse of the platform margin, possibly induced by synsedimentary extensional faulting (Graziano, , ; Borgomano, ).…”
Section: Study Area and Methodologymentioning
confidence: 99%
“…These authors accordingly suggested that these latter regions had escaped the effects of eutrophication fuelled by enhanced continental weathering which, according to their model, had caused the demise of the northern platforms. Yet this model left two key points unexplained: firstly, the evidence that OAE 1a also affected facies on the isolated Apulian Platform and even on such remote oceanic platforms as Resolution Guyot, in the Pacific (Graziano, 1999; Jenkyns & Wilson, 1999), not just those close to continental hinterlands; and, secondly, the mass extinction of platform biota recorded by Masse (1989) reached its finale at the end, not the middle of the Early Aptian (Fig. 2) – an observation that has stood the test of subsequent biostratigraphical refinement (Masse, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The Valanginian nannoconid decline occurred before and throughout the first major perturbation in the Cretaceous carbon cycle, the so-called "Weissert Event" or episode Charbonnier et al, 2013) defined by a global positive excursion, in marine carbonate-and marine and terrestrial organiccarbon isotope records (Cotillon and Rio, 1984;Lini et al, 1992;Channell et al, 1993;Föllmi et al, 1994;Weissert et al, 1998;Hennig et al, 1999;Wortmann and Weissert, 2001;Gröcke et al, 2005;Duchamp-Alphonse et al, 2007;Bornemann and Mutterlose, 2008). It coincided with several phases of carbonate platform drownings (Schlager, 1989;Föllmi et al, 1994;Graziano, 1999;Föllmi et al, 2006) and overall turnovers and crises in pelagic and neritic carbonate biota (Channell et al, 1993;Kaim, 2001;Bersezio et al, 2002;Janssen and Clément, 2002;Erba and Tremolada, 2004;Duchamp-Alphonse et al, 2007;Barbarin et al, 2012). Interestingly, no widespread anoxia is observed (Westermann et al, 2010;Kujau et al, 2012), although sometimes, black shales are found in the Tethys and Pacific Oceans .…”
Section: Introductionmentioning
confidence: 99%